FRANCIS BACON ON THE RELATIONSHIP BETWEEN SCIENCE AND RELIGION - Aminova Nargiza Sharifovna (Scholar Express Journal, 2023)
The article provides information about Bacon's religious position, about the steps in the development of the human mind, about how a scientist subordinates the mind to religion, which means that he makes human arbitrariness fall silent before divine arbitrariness
Keywords: divine arbitrariness; fruitless verbiage; deism; metaphysics